(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article author analyzes concept of fault according to philosophical approach. In philosophies fault and responsibility are expressed as identical categories. It is impossible to consider responsibility in this branch of science in a separation from guilt of the person, and vice versa (the person is responsible before by itself, before society, before god). The author carries out the analysis to the available opinions concerning concept of fault of ancient philosophy, medieval philosophy and philosophy of modern times. In a general view, the fault in philosophy needs to be as category of ethics and moral. Key words: psychoanalytic concept of fault, teotsentrizm, bikhevioristichesky theory, existential and humanistic concept.